Decarboxylative sulfonylation of arylpropiolic acids with sulfinic acids: synthesis of (E)-vinyl sulfones - Jatuporn Meesin (2018)
© 2016 Elsevier Ltd. Decarboxylative sulfonylation of arylpropiolic acids has been achieved by simply employing Na2CO3as a promoter and arenesulfinic acids as sulfonylating reagents. This simple and environmentally benign transformation offers an alternative approach and allows for easy and rapid synthesis of E-Vinyl sulfones from arylpropiolic acids and arenesufinic acids.